Capture—Incubate—Release: An Animal‐Friendly Approach to Assess Local Aquatic Macroinvertebrate Species Diversity Through Environmental DNA Metabarcoding - Mandy Sander; Arne J. Beermann; Dominik Buchner; Martina Weiss; Marie‐Thérése Werner; Florian Leese (Environmental DNA, 2025)
ABSTRACT Metabarcoding of environmental DNA (eDNA) from water samples has become an important tool for aquatic biodiversity assessment because it is minimally invasive, time‐efficient, and generates comprehensive taxa lists. Nevertheless, species lists differ noticeably from those obtained via bulk metabarcoding of the local benthic community because of eDNA traces transported in the water column. However, it is important for several assessments to capture local biodiversity signals. Our goal was to test whether we can combine the advantages of both methods, that is, obtaining a local signal and being minimally invasive. Therefore, our developed method includes capturing local benthic invertebrates, incubating them in a water container for eDNA enrichment and analysis, and releasing them back to their habitat. We first quantified eDNA release over time for 10 invertebrate species in a laboratory setting using qPCR. We found that a 5‐min incubation is sufficient to successfully detect 50% of the replicates for six of the 10 species. Three of the species showed a significant increase in eDNA molecules over time. However, the experiment showed a species‐specific eDNA release pattern that was not directly linked to body sclerotization nor biomass. As a second experiment, we sampled bulk samples at three field sites and incubated the bulk samples for 0, 20, 40, and 80 min in containers filled with stream water to compare taxa lists obtained via metabarcoding of bulk and the enriched eDNA samples. Our results showed a much higher overlap between bulk and enriched eDNA metabarcoding (55%–60%) in comparison to reported overlaps between bulk and stream eDNA metabarcoding from other studies (often < 20%). This overlap did not change with incubation time. Thus, our study demonstrates that it is possible to detect most locally occurring species via eDNA metabarcoding after shortly incubating them in water. Therefore, this approach has great potential for point‐sample eDNA analysis of macroinvertebrates without compromising animal welfare.